Mathematical Modelling and Experimental Analysis of Thin, Low-Loading Fuel Cell Electrodes. (14th September 2015) - Secanell, Marc; Putz, Andreas; Shukla, Shantanu; Wardlaw, Phillip; Bhaiya, Madhur; Pant, Lalit M.; Sabharwal, Mayank
Abstract : Cathode electrode performance quickly degrades at platinum loadings below 0.1 mg/cm 2 . This performance degradation has been attributed to catalyst oxide coverage, local micro-scale gas transport limitations at the catalyst sites, and two-phase flow. OpenFCST, an open-source fuel cell simulation package, is used to develop a membrane electrode assembly (MEA) model, and a catalyst layer micro-structural model, of low loading inkjet printed fuel cells. Simulations of the inkjet printed catalyst layer reconstructions estimate that the effective gas transport in the electrode is of the order of 10 -4 cm 2 /s and it is dominated by Knudsen diffusion. The macro-scale MEA mathematical model is used to estimate cell performance, cell and catalyst layer ohmic resistances, and current, reactant and oxide coverage distributions in the electrode. MEA model cell performance and resistance are in reasonable agreement with experimental data obtained for the electrodes under a variety of oxygen partial pressures. Results show appropriate kinetic, and local transport resistance models, are necessary in order to capture the experimental trends observed at different loadings and at limiting current densities, respectively.